Complete sequencing by Pyrosequencing of APOB gene of patients with clinical diagnosis of Familial Hypercholesterolaemia - Alves, A.C. (2012)
Familial hypercholesterolemia (FH) is a monogenic condition caused in most cases by mutations in LDLR gene, but mutations in APOB and PCSK9 genes are also cause of FH. These 3 genes are currently studied in the “Portuguese FH Study”. From the 404 families with a clinical diagnosis of FH studied, only 48% of these have a detectable mutation in the 3 genes mention above so, other mutations in these genes or other gene defects must exist to explain the cause of hypercholesterolemia in the remaining families. The main aim of this project was the whole sequencing of APOB gene, in 65 index patients with clinical diagnosis of FH, without mutations in LDLR gene or in fragments of exon 26 and 29 of APOB gene, by pyrosequencing, in order to identify the genetic cause of the hypercholesterolemia in these patients. A pool of the 65 DNAs was sequenced by pyrosequecing method and a total of 227688 nucleotide reads were obtained, corresponding to a mean coverage of 35x/fragment/individual. The results obtained included the detection of 87 alterations, being 27 previously described SNPs. All patients were re-sequenced for the fragments containing exons 26 and 29 alterations identified by this method. From the 26 alterations detected in these exons, only 12 were found and four of these had not been previously described. After family studies only one alteration did not co-segregate in the family, providing further evidence that 3 of the alterations found can be mutations causing disease but, functional studies are required to prove pathogenicity. Pyrosequencing allows the rapid sequencing of a large number of individuals, but apart from its high cost, it has some limitations and requires an improvement of technique.